Numerical analysis and experimental research on hard rock fragmentation by high voltage pulse discharge. (1st July 2021) - Che, Long; Gu, Xiaohui; Li, Hongda
Graphical abstract: Highlights: The electric field and breakdown effect of gypsum reduce with electrodes gap increasing. Rock types largely determine the effect of rock fragmentation. Electrons field analysis can also obtain similar results about influence factors. The impact of positive electrode is more obvious than negative one for crushing effect of hard rock samples. Abstract: To investigate influence factors of hard rock fragmentation, numerical simulation and experimental research of hard rock breaking by high voltage pulse discharge are examined by two parameters: electrode gap and hard rock type. Using the three-dimensional electromagnetic simulation software Computer Simulation Technology, the electric field distribution of the electrode and variation of motion trajectory of discharge particles within the hard rock are simulated. Breaking hard rocks by high voltage pulse discharge experiments are carried out to observe the breakage effect of hard rock and the waveforms of output voltage and current. The results show that the fragmentation effect of hard rock is strongly dependent on the electrode gap and rock type, and experimental results are consistent with the simulations. The above conclusions provide appropriate conditions for the subsequent application of high voltage pulse discharge in hard rock fragmentation.